Law Enforcement Analysis Against Online Prostitution Brokers Through The Michat Application: A Study At The Cibinong District Court - Islam, Alviansyah Ikhwanul; Hartini, Sri; Purwaningsih, Prihatini (JURNAL MAHASISWA YUSTISI, 2024)
This research is motivated by crimes that are developing along with advances in technology, namely online prostitution via social media, namely the michat application which is often misused by pimps and commercial sex workers (PSK) in carrying out the practice of the act. online prostitution crime. This research is research on law enforcement of the criminal act of online prostitution pimping (study at Cibinong District Court). This research aims to understand the process of criminal procedural law against perpetrators of criminal acts of pimping and to find out how judges make decisions regarding criminal acts of pimping. This research uses a normative juridical method, with a descriptive analytical problem approach, the secondary data used is a copy of the court decision, where the data that has been obtained is analyzed using qualitative methods. The results of the research show that the criminal procedural legal process for perpetrators of the crime of online prostitution pimping goes through stages. - stages regulated in the Criminal Procedure Code. After the investigation, the case will be submitted to court and the trial process will take place. In the trial process, evidence and facts related to the online prostitution pimping case will be tested to determine whether the perpetrator is guilty or not. Based on the results of research that has been carried out, it shows that AZ as the defendant has committed the crime of online prostitution pimping, the Court stated that the defendant was legally and convincingly proven to have committed the crime by intentionally and without the right to distribute electronic information that had content that violated decency as in the first indictment. The punishment given is imprisonment for 1 year and 6 months and a fine of Rp. 100,000,000. If the fine is not paid, it will be replaced by imprisonment for 2 months. The period of arrest and detention of the defendant is deducted entirely from the sentence imposed.